Prequel : an American fight against Fascism - Maddow, Rachel (Crown, 2023)
Rachel Maddow traces the fight to preserve American democracy back to World War II, when a handful of committed public servants and brave private citizens thwarted far-right plotters trying to steer our nation toward an alliance with the Nazis. Inspired by her research for the hit podcast Ultra, Rachel Maddow charts the rise of a wild American strain of authoritarianism that has been alive on the far-right edge of our politics for the better part of a century. Before and even after our troops had begun fighting abroad in World War II, a clandestine network flooded the country with disinformation aimed at sapping the strength of the U.S. war effort and persuading Americans that our natural alliance was with the Axis, not against it. It was a sophisticated and shockingly well-funded campaign to undermine democratic institutions, promote antisemitism, and destroy citizens' confidence in their elected leaders, with the ultimate goal of overthrowing the U.S. government and installing authoritarian rule. That effort worked--tongue and groove--alongside an ultra-right paramilitary movement that stockpiled bombs and weapons and trained for mass murder and violent insurrection. At the same time, a handful of extraordinary activists and journalists were tracking the scheme, exposing it even as it was unfolding. In 1941 the U.S. Department of Justice finally made a frontal attack, identifying the key plotters, finding their backers, and prosecuting dozens in federal court. None of it went as planned. While the scheme has been remembered in history--if at all--as the work of fringe players, in reality it involved a large number of some of the country's most influential elected officials. Their interference in law enforcement efforts against the plot is a dark story of the rule of law bending and then breaking under the weight of political intimidation. That failure of the legal system had consequences. The tentacles of that unslain beast have reached forward into our history for decades. But the heroic efforts of the activists, journalists, prosecutors, and regular citizens who sought to expose the insurrectionists also make for a deeply resonant, deeply relevant tale in our own disquieting times.